2006
DOI: 10.1111/j.1600-9657.2006.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Does hard insertion and space improve shock absorption ability of mouthguard?

Abstract: Mouthguards are expected to reduce sports-related orofacial injuries. Numerous studies have been conduced to improve the shock absorption ability of mouthguards using air cells, sorbothane, metal wire, or hard material insertion. Most of these were shown to be effective; however, the result of each study has not been applied to clinical use. The aim of this study was to develop mouthguards that have sufficient prevention ability and ease of clinical application with focus on a hard insertion and space. Ethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(110 citation statements)
references
References 14 publications
6
83
0
6
Order By: Relevance
“…In earlier studies (21,22), we attempted to develop a mouthguard with sufficient injury prevention ability and ease of clinical application. This mouthguard consisted of an outer and an inner EVA layer and a middle layer of acrylic resin (hard insert), with a space to prevent contact between the inner surface of the mouthguard and the buccal surfaces of the maxillary anterior teeth, which often receive direct horizontal impact in sports and in more than 80% of sports-related tooth injuries (23)(24)(25)(26)(27), or teeth already weakened through prior damage or treatment(7-10)).…”
Section: Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies (21,22), we attempted to develop a mouthguard with sufficient injury prevention ability and ease of clinical application. This mouthguard consisted of an outer and an inner EVA layer and a middle layer of acrylic resin (hard insert), with a space to prevent contact between the inner surface of the mouthguard and the buccal surfaces of the maxillary anterior teeth, which often receive direct horizontal impact in sports and in more than 80% of sports-related tooth injuries (23)(24)(25)(26)(27), or teeth already weakened through prior damage or treatment(7-10)).…”
Section: Outlinementioning
confidence: 99%
“…This mouthguard consisted of an outer and an inner EVA layer and a middle layer of acrylic resin (hard insert), with a space to prevent contact between the inner surface of the mouthguard and the buccal surfaces of the maxillary anterior teeth, which often receive direct horizontal impact in sports and in more than 80% of sports-related tooth injuries (23)(24)(25)(26)(27), or teeth already weakened through prior damage or treatment(7-10)). These mouthguards showed more than 95% shock absorption ability in terms of tooth distortion against impact with a steal ball carrying 15.2 kgm 2 /S 2 potential energy (21,22).…”
Section: Outlinementioning
confidence: 99%
“…The Federation Dentaire Internationale issued the policy statements that national dental associations promote to the public and to oral health care professionals the benefits of sports mouthguards, including the prevention of orofacial injuries 5) . Mouthguard materials should have the ability to absorb and disperse impact energy to avoid concentrating force around an impact point, and should be durable throughout the season 6,7) . Most mouthguards currently comprise ethylene-vinyl acetate copolymer (EVA).…”
Section: Introductionmentioning
confidence: 99%
“…Takeda et al indicated that mouth guards incorporating a hard insert and buffering space improved their shock absorption ability [26–30]. The concept consisted of using a deformation of the hard insert (similar to a structural feature termed a crumple zone or crush space used in automobiles) to absorb and diffuse the energy of the impact away from the most important area, for example, maxillofacial traumatic injured area (or tissue) and/or the most dangerous area, for example, maxillary anterior teeth.…”
Section: Introductionmentioning
confidence: 99%